Deciphering codon usage patterns and evolutionary forces in chloroplast genes of Camellia sinensis var. assamica and Camellia sinensis var. sinensis in comparison to Camellia pubicosta - Sophiarani Yengkhom; Arif Uddin; Supriyo Chakraborty (Journal of Integrative Agriculture)
Codon usage bias (CUB) is a unique property of genome which refers to non-random usage of synonymous codons in coding sequences. The present study makes an attempt to find out the pattern of CUB in chloroplast (cp) genes among three tea species, i.e., Camellia sinensis var. assamica (Assam tea), Camellia sinensis var. sinensis (Chinese tea) and Camellia pubicosta (wild tea species) as no work on CUB was reported earlier. To understand the patterns of codon usage among the cp genes of three tea groups, we used bioinformatic tools to investigate the protein coding sequences of cp genes. In our present study, the mean nucleobase T was the highest whereas C was the lowest in all the three tea groups. The overall AT content was more than GC content, i.e., genes were AT rich. The scaled chi-square (SCS) value indicated that the CUB of cp genes was low. The codon CGT (Arg) was over-represented in C. sinensis var. sinensis whereas GGA (Pro) was over-represented in C. pubicosta species. Heatmap study revealed that most of the GC ending codons showed positive correlations between codon usage and GC3 while AT ending codons exhibited negative correlations. From neutrality plot analysis, it was evident that natural selection had played a major role, while mutation pressure exerted a minor effect in the CUB of cp genes in three tea groups. Highly significant (P<0.01) positive correlation was found between SCS and synonymous codon usage order (SCUO) of cp genes which suggested that high expression of cp genes was associated with high degree of CUB.